Peran Psychosocial Safety Climate pada Psychological Distress dan Job Satisfaction Pada Pekerja Shift Di Industri Manufaktur FMCG - Mauliana Maharani, Aisya; Hikmat Ramdhan, Doni (Jurnal Locus Penelitian dan Pengabdian, 2026)
Work environment in Fast-Moving Consumer Goods (FMCG) manufacturing sector has crucial role as pillar of economic activity. The mass and continuous production require this sector having shift work systems. This systems expose employees to significant physical and psychological demands due to irregular working hours. These conditions may trigger potential conflict in both work and family domains, as the result of unstable psychological can affect employee well-being. This study aims to analyse the relation of Psychosocial Safety Climate (PSC) on Psychological Distress, and Job Satisfaction (JSS) among FMCG industry employees in Indonesia. This research using a quantitative design with a cross-sectional approach. Data were collected through PSC-12, Kessler Psychological Distress Scale (K10), and Job Satisfaction Scale. Total of 77 respondents working in FMCG manufacturing in Bekasi Regency participated in this research. The findings show no relation between PSC and psychological distress (r = -0.138). In contrast, PSC was positively associated with JSS (r = 0.534), and JSS was negatively associated with distress (r = -0.303).